Effectiveness of using video tutorial-based learning media in the SMAW welding techniques course - Fadli Gunawan; Bulkia Rahim; Fathir Aspar; Dori Yuvenda (Universitas Negeri Padang, 2026)
This study examined the effectiveness of video tutorial–based learning media in improving students’ mastery of horizontal-position Shielded Metal Arc Welding (SMAW) in a technical and vocational education and training (TVET) context. The study responded to the limited evidence on position-specific digital instructional media in welding education, particularly for horizontal-position SMAW practice, which requires precise control of movement, angle, and bead formation. A pre-experimental one-group pretest-posttest design was employed involving 30 Grade XI students in the Mechanical Engineering program at SMKN 1 Sumatera Barat. Data were collected using a validated 30-item performance assessment covering preparation, process, and final weld quality, and were analyzed using descriptive statistics and a paired-samples t-test in IBM SPSS Statistics. The results showed a substantial improvement in students’ performance after the intervention. The mean score increased from 47.57 in the pre-test to 81.70 in the post-test, with a mean gain of 34.13 points. The paired-samples t-test revealed a statistically significant difference, t(29) = 15.25, p < 0.001, and the effect size was very large (d = 2.78). These findings indicate that video tutorial–based media can serve as an effective, low-cost, and scalable instructional tool for procedural welding skills. The study contributes to digital pedagogy in TVET by highlighting the importance of pedagogical fit in technology-supported practical instruction.